2015
DOI: 10.1021/jacs.5b06576
|View full text |Cite
|
Sign up to set email alerts
|

An Arylative Ring Expansion Cascade of Fused Cyclobutenes via Short-Lived Intermediates with Planar Chirality

Abstract: An arylative ring expansion cascade has been developed for the synthesis of medium-sized carbocycles from fused cyclobutenes. This reaction proceeds through a short-lived cis,trans-cycloalkadiene intermediate that is formed by thermal 4π electrocyclic ring opening. Chirality transfer experiments provide direct evidence for the transient generation of the intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Having developed ad irect approacht oa minocyclobutenol derivatives 5a-q and 6a-f as single isomers from ynamides, we were then interested in using the inherentr ing strain [11] of these highly functionalized four-membered carbocycles to perform as electivec arbon-carbon bond fragmentation as an ew entry to aminoalkenes. Attempts to generate ar ing-opened structure from 5c in refluxing benzene failed.…”
Section: Resultsmentioning
confidence: 99%
“…Having developed ad irect approacht oa minocyclobutenol derivatives 5a-q and 6a-f as single isomers from ynamides, we were then interested in using the inherentr ing strain [11] of these highly functionalized four-membered carbocycles to perform as electivec arbon-carbon bond fragmentation as an ew entry to aminoalkenes. Attempts to generate ar ing-opened structure from 5c in refluxing benzene failed.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Takasu and co-workers reported an elegant domino arylative ring expansion of fused optically pure cyclobutenes 52 toward the synthesis of medium ring-fused trans-indolines 53. 21 The complete trans-diastereoselectivity of products was due to the planar rigidity of the trans diene derived from thermal 4-electrocyclic ring opening/ expansion of 52 (n = 1) (Scheme 18). The ring expansion of the unstable bicyclic units generating trans-diene int-B and its intermolecular trapping with the aryl-Pd complex…”
Section: Review Synthesismentioning
confidence: 99%
“…trans-Cyclononene derivatives, such as 100, can be prepared by a 4π electrocyclic ring opening reaction from a cis-fused cyclobutene (101), progressing via a cis,trans-siloxycycloalkadiene intermediate (102), with yields of up to 92 % (Scheme 34). [103,104] The reaction conditions were investigated and it was reported that the torquoselectivity during cyclobutene ring opening was highly controlled by an electron-donating siloxy-substituent, resulting in a proceeding Heck reaction to be regioselective on the distorted trans-double bond. A second synthesis of trans-cyclononene derivatives has been reported by Larionov and Corey, who used this compound in the synthesis of -Caryophyllene 103 (Scheme 35), which is a natural product that contains a trans-cyclononene core.…”
Section: Trans-cyclononenementioning
confidence: 99%